Pregnant Women's Knowledge Affects Regularity Consumption Addition Blood Tablet to Prevent Anemia with Lawrence Green Theoretical Approach - Nurul Khalifah; Gunarmi Gunarmi; Hargianti Dini Iswandari (Indonesian Journal of Global Health Research, 2025)
Anemia during pregnancy is problem health serious society​ Because impact on the mother and fetus , including risk bleeding and death. Therefore That needed good knowledge​ For prevent anemia. This research purpose for analyze influence knowledge to regularity Mother pregnant in taking supplements tablets blood based on Lawrence Green's theory. Research conducted on 75 mothers pregnant at the health center Kalianget and Lenteng , Regency Sumenep . Methods used is observational analytic with cross sectional approach. Observation of variables is not on the same day and time but is taken at one time, namely data on knowledge and consumption of blood-boosting tablets. Data analysis using regression simple. The results show P value = 0.000 that knowledge influential significant to regularity consumption of supplement blood tablets.This research recommend improvement education in service pregnancy as a prevention strategy anemia.